BROADBAND ANTENNA RESPONSE USING HYBRID TECHNIQUE COMBINING FREQUENCY DOMAIN MoM AND FDTD - Alhameed, R.A. Abd-; Excell, P.S.; Mangoud, M.A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A hybrid technique is proposed for computation of broadband characteristics of an antenna in the presence of a dielectric scatterer. The technique links the frequency domain Method of Moments (MoM) and the Finite Difference Time Domain (FDTD) method. The coupling of these methods is achieved by using the Equivalence Principle, applied over the intervening surface. A great reduction in computation time is achieved in the MoM domain by using an impedance interpolation technique. The Gaussian pulse (GP) and Derivative Gaussian pulse (DGP) are investigated as the excitation sources for the MoM. Examples are given and the results found to be in good agreement with alternative methods.